The Alkene Monooxygenase from Xanthobacter Strain Py2 Is Closely Related to Aromatic Monooxygenases and Catalyzes Aromatic Monohydroxylation of Benzene, Toluene, and Phenol - Zhou, Ning-Yi (American Society for Microbiology, 1999)
The genes encoding the six polypeptide components of the alkene monooxygenase from Xanthobacter strain Py2 (Xamo) have been located on a 4.9-kb fragment of chromosomal DNA previously cloned in cosmid pNY2. Sequencing and analysis of the predicted amino acid sequences indicate that the components of Xamo are homologous to those of the aromatic monooxygenases, toluene 2-, 3-, and 4-monooxygenase and benzene monooxygenase, and that the gene order is identical. The genes and predicted polypeptides are aamA, encoding the 497-residue oxygenase α-subunit (XamoA); aamB, encoding the 88-residue oxygenase γ-subunit (XamoB); aamC, encoding the 122-residue ferredoxin (XamoC); aamD, encoding the 101-residue coupling or effector protein (XamoD); aamE, encoding the 341-residue oxygenase β-subunit (XamoE); and aamF, encoding the 327-residue reductase (XamoF). A sequence with >60% concurrence with the consensus sequence of ς(54) (RpoN)-dependent promoters was identified upstream of the aamA gene. Detailed comparison of XamoA with the oxygenase α-subunits from aromatic monooxygenases, phenol hydroxylases, methane monooxygenase, and the alkene monooxygenase from Rhodococcus rhodochrous B276 showed that, despite the overall similarity to the aromatic monooxygenases, XamoA has some distinctive characteristics of the oxygenases which oxidize aliphatic, and particularly alkene, substrates. On the basis of the similarity between Xamo and the aromatic monooxygenases, Xanthobacter strain Py2 was tested and shown to oxidize benzene, toluene, and phenol, while the alkene monooxygenase-negative mutants NZ1 and NZ2 did not. Benzene was oxidized to phenol, which accumulated transiently before being further oxidized. Toluene was oxidized to a mixture of o-, m-, and p-cresols (39.8, 18, and 41.7%, respectively) and a small amount (0.5%) of benzyl alcohol, none of which were further oxidized. In growth studies Xanthobacter strain Py2 was found to grow on phenol and catechol but not on benzene or toluene; growth on phenol required a functional alkene monooxygenase. However, there is no evidence of genes encoding steps in the metabolism of catechol in the vicinity of the aam gene cluster. This suggests that the inducer specificity of the alkene monooxygenase may have evolved to benefit from the naturally broad substrate specificity of this class of monooxygenase and the ability of the host strain to grow on catechol.